Entrepreneurship in a global context - Birley, Sue.; MacMillan, Ian C., 1940-; Insead; Global Conference on Entrepreneurial Research 1994 : Fontainebleau, France) (London ; New York : Routledge, 1997)
This collection presents selected papers from the Fourth Annual Global Conference on Entrepreneurial Research, held in 1994 at INSEAD, France.
Book Cover; Title; Contents; List of figures; List of tables; List of contributors; Introduction; STRONG TIES, WEAK TIES AND STRANGERS: DO WOMEN OWNERS DIFFER FROM MEN IN THEIR USE OF NETWORKING TO OBTAIN ASSISTANCE?; THE DETERMINATION OF OPTIMAL MARKETING EXPENDITURES: AN APPLICATION OF OPTION THEORY; UNFINISHED BUSINESS: OBSTACLES TO ENTREPRENEURSHIP IN THE REFORM OF STATEOWNED ENTERPRISES IN CHINA AND VIETNAM; CREATING VALUE ON THE BALANCE SHEET: CAPITAL STRUCTURES OF NEW BUSINESSES; COPING WITH INDUSTRY TRANSFORMATION: THE CASE OF THE ITALIAN TANNERY INDUSTRY.
Selected papers from the Fourth Annual Global Conference on Entrepreneurship Research, held in 1994 at INSEAD, France.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: International business enterprises -- Management -- Congresses; Entrepreneurship -- Congresses; International business enterprises -- Management -- Congresses; Entrepreneurship -- Congresses; Entreprises multinationales -- Gestion -- Congrès.; Entrepreneuriat -- Congrès.; Entreprises multinationales -- Gestion -- Congrès.; Entrepreneuriat -- Congrès.; BUSINESS & ECONOMICS -- Entrepreneurship; Entrepreneurship; International business enterprises -- Management; Ondernemingsgeest; Internationalisatie; Ondernemerschap; Electronic books; proceedings (reports); Conference papers and proceedings; Congressen (vorm); Conference papers and proceedings; Actes de congrès.